MODEL BISNIS TAMAN NASIONAL MANDIRI: KASUS TAMAN NASIONAL GUNUNG PALUNG KALIMANTAN BARAT - Hendra Gunawan; Sambas Basuni; Pandu Wirawan Arief (Department of Forest Resources Conservation and Ecotourism - IPB University, 2013)
Management of national park has been facing problems due to budgeting limitation. One of the idea to reorient conservation areas management from cost center to profit center is developing self finance national park. The objectives of this research were aimed to describe business model of Gunung Palung National Park; to construct business model of self-finance Gunung Palung National Park, and to formulate development strategy toward self-finance of Gunung Palung National Park. The research used business model canvas analysis. The results showed that business model of Gunung Palung National Park has strengths in addressing weaknesses in each of the components and can take advantage of opportunities to fine-tune its business model. Business model of self finance Gunung Palung National Park was categorized as business to business (B2B) model which sold products and services by partner companies. Keywords : business model, environment condition, Gunung Palung National Park